Evaluation of the end-to-end TCP performance for vertical handover using intermediate switching network. (1st January 2014) - Yadav, Aditya; Barooah, Maushumi; Chakraborty, Sandip; Nandi, Sukumar; Ahuja, Sanjay
Most of the traffic in today's network uses the transmission control protocol (TCP) as the transport layer protocol for reliable end-to-end packet delivery. However, TCP considers packet loss to be the result of network congestion which makes it unsuitable for mobile wireless communication, where sporadic and temporary packet losses are usual due to fading, shadowing, hand-off and other radio effects. During the vertical hand-off between different wireless technologies, the problem of end-to-end connection and reliability management for TCP becomes more severe. Intermediate switching network (ISN) is an effective framework for vertical handover between the UMTS and the WLAN network. This paper evaluates the performance of TCP over ISN-based framework. The proposed scheme uses a cross layer interaction between the data link and the transport layers to estimate TCP retransmit timeout and congestion window during handover. Simulation results establishes effectiveness of the proposed scheme.